Character Building of Discipline and Responsibility Through the Qur'an Tahfidz Program for Class IV Students at Mi Terpadu Al-ladunni purwosari - Aisah, Siti; Kirom, Askhabul; Saifulah, H. (Sean Institute, 2023)
The character of discipline and responsibility is very important in instilling and shaping the character of students in the tahfidz al-Qur'an program at MI Integrated Al-Laduunni.The character of discipline and responsibility is very important to be instilled in students in schools as places of formal education. The approach used in this research is descriptive qualitative. The process includes observation methods, interviews, and documentation. The results of this study indicate that: (1) The formation of the character of discipline and responsibility through the tahfidz al-Qur'an program has gone well, (2) Supporting factors include professional teacher motivation that can shape student character and inhibiting factors include friends, family and environmental factors